United States Chiropractic Practice Acts and Institute of Medicine defined primary care practice - Duenas, Richard (Elsevier, 2002)
OBJECTIVE: This review was conducted to analyze the law for the practice of chiropractic throughout the United States, including the District of Columbia, Puerto Rico and the U.S. Virgin Islands, to determine the legal ability of the Doctor of Chiropractic in each jurisdiction to provide primary care service as described by the 1996 Institute of Medicine Definition of Primary Care. METHOD: The practice acts for each State, the District of Columbia, Puerto Rico and the U.S. Virgin Islands were reviewed for language that would permit the chiropractic doctor to meet the 9 criteria of primary care practice described by the Institute of Medicine. Forty-four practice acts were cross referenced with the results of a scope of practice survey of State Boards of Chiropractic in 1999. RESULTS: The review of the practice acts and the survey on chiropractic scope of practice revealed a varied degree of chiropractic scope of practice with 23 of 53 of the jurisdictions limiting the ability of the chiropractic doctor to fully provide IOM defined primary care. CONCLUSION: The varied practice act definitions for chiropractic practice throughout the United States the District of Columbia, Puerto Rico and the U.S. Virgin Islands reveal an inability of the chiropractic profession to respond to a call for a standard nationally-based primary-care policy that could be readily achieved by all chiropractic practitioners throughout the Union. This void of primary-care qualification in many State and Commonwealth practice acts will need to be addressed by the leaders of the profession if government entities and national third party organizations are to utilize chiropractic health care services to the standard of chiropractic education and clinical experience. The need for a broad range chiropractic scope of practice model practice act is suggested.